Aplikasi Bakteri Bacillus Thuringiensis Dan Petrogenol Pada Tanaman Buah Di Kampung Sukamaju Distrik Malind Kabupaten Merauke Papua Selatan - sembiring, jefri; Pongkendek, Jesi Jecsen; Kusumah, Rangga; Mendes, Johana; Anwar, Anwar; Yusuf, Mani; Sarijan, Abdullah (Journal Of Human And Education (JAHE), 2024)
Integrated Pest Management (IPM) is a pest population control system that uses all control methods to reduce and maintain populations below the level of economic damage. Pest and disease attacks on fruit plants become obstacles, making production unstable. In addition, the increasing pest population is followed by increasing production costs, which impact decreasing farmer income. Fruit farmers who have just started cultivating fruit plants have complex problems facing pest and disease attacks, especially Fruit Flies and Spodoptera sp. The purpose of this service is to provide information on IPM technology in controlling pests and diseases in fruit plants, especially the use of Bacillus thuringiensis Microorganisms and petrogenol in the Sukamaju Village farmer group, Malind District, Merauke Regency to control pests and diseases. The community service approach involves stages of introduction/socialization, training, and technology implementation, which involves active participation from group members. The results of this service are expected to increase farmers' knowledge, attitudes, and actions regarding the use of insecticides against plant pests. The evaluation results show that knowledge about natural enemies and using biological insecticides and traps as a reference for integrated pest control (IPM) has started to improve. In addition, the community can already use environmentally friendly technology, namely Bacillus thuringiensis and petrogenol. It is hoped that increased knowledge will be followed by an increase in the attitudes and actions of farmers in controlling pests and plant diseases, including the use of pesticides that are wiser and more environmentally friendly Keywords: Bacillus thuringiensis, Fruit Fly, Merauke, Petrogenol, Spodoptera sp